La educación constructivista en su relación con el proceso de secularización - Ponce, Manuel Ocampo (Sapientia, 2022)
In recent decades, constructivists have developed a number of educational and technological resources to disseminate their methods. The problem lies in the fact that the common denominator of construction theories is that they start by denying the human intellectual faculty to guarantee sufficient knowledge of objective reality. So-called construction theories, such as educational constructivism and social constructionism, have prioritized the subject at the cost of an implicit denial of the truth, which ends up being postulated as a social construct. From that perspective, they have contributed to the process of secularization with multiple family, political, social, and cultural consequences. In this brief work, some elements of the relationship between the theories of construction and the secularization process are shown. These also have a relationship with liberal capitalism and socialist communism.